2018
DOI: 10.3389/fpsyg.2018.00162
|View full text |Cite
|
Sign up to set email alerts
|

One Way or Another: Evidence for Perceptual Asymmetry in Pre-attentive Learning of Non-native Contrasts

Abstract: Research investigating listeners’ neural sensitivity to speech sounds has largely focused on segmental features. We examined Australian English listeners’ perception and learning of a supra-segmental feature, pitch direction in a non-native tonal contrast, using a passive oddball paradigm and electroencephalography. The stimuli were two contours generated from naturally produced high-level and high-falling tones in Mandarin Chinese, differing only in pitch direction (Liu and Kager, 2014). While both contours h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 119 publications
1
7
0
Order By: Relevance
“…But only some languages also make use of lexical tones , contrastive sub-syllabic fundamental frequency (pitch) variations referred to as tonemes (e.g., Jones, 1944), which for those languages comprise a third class of phonemic elements. Perceptual researchers often assume tones to be suprasegmental (e.g., So and Best, 2010, 2011, 2014; Liu et al, 2018; Poltrock et al, 2018), i.e., to extend across the consonants and vowels of the target syllable. While in a phonetic sense tones extend across the voiced segments of a syllable, however, such observations may not straightforwardly reflect the more abstract phonological properties of tones (e.g., see Wang, 1967; Hyman, 2011a,b).…”
mentioning
confidence: 99%
“…But only some languages also make use of lexical tones , contrastive sub-syllabic fundamental frequency (pitch) variations referred to as tonemes (e.g., Jones, 1944), which for those languages comprise a third class of phonemic elements. Perceptual researchers often assume tones to be suprasegmental (e.g., So and Best, 2010, 2011, 2014; Liu et al, 2018; Poltrock et al, 2018), i.e., to extend across the consonants and vowels of the target syllable. While in a phonetic sense tones extend across the voiced segments of a syllable, however, such observations may not straightforwardly reflect the more abstract phonological properties of tones (e.g., see Wang, 1967; Hyman, 2011a,b).…”
mentioning
confidence: 99%
“…This means that the brain does not wait until S2 is fully recognized before it starts to entertain the possibility of parsing S1 as an underlying T3. Pre-attentive learning and the development of expectations (Bendixen et al, 2012 ; Liu et al, 2018 ) in an MMN experiment with repeated exposure might explain the early onset of the UR Relation effect as well. After all, participants heard only two lexical items in one sub-block, and there were only four lexical items in our experiment (see the Methods section).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies attempted to capture the effect of passive exposure on auditory change detection mechanisms. Studies with word stimuli showed that passive exposure may lead to enhanced MMN for novel tonal contrasts or tonal word-forms within a single experimental session (Liu, Ong, Tuninetti, & Escudero, 2018;Yue, Bastiaanse, & Alter, 2014).…”
Section: Limitationsmentioning
confidence: 99%